Indonesia Space Program : Future Soft Power - Murdi Primbani; Eman Hermawan (CV. Syntax Corporation Indonesia, 2024)
This paper discusses Indonesia's space / aerospace industry program as the nation's future Soft Power. The term 'soft power', coined by Joseph S. Nye of Harvard University in the United States, is the ability of a country to influence another country not through coercive means but through attractiveness or reputation. This research uses a literature research approach, which is a method by collecting data by understanding and studying theories from various literature related to research There are four stages of literature study in research. Space, or simply space, is the expanse that exists beyond the Earth and between celestial bodies. Space isn't completely empty it's a hard vacuum containing low particle densities, especially hydrogen and helium plasma, as well as electromagnetic radiation, magnetic fields, neutrinos, dust, and cosmic rays. Recent developments show that in the future, not only professional astronauts can go into space but also all citizens of the world can afford to pay.